Effect of a ring electrode on the cone-jet characteristics of ethanol in small-scale electro-spraying combustors. (August 2016) - Gan, Yunhua; Zhang, Xia; Li, Haige; Tong, Yang; Zhang, Yang; Shi, Yanling; Yang, Zeliang
Abstract: Two new micro-scale electro-spraying combustors of nozzle-grid and nozzle-ring-grid electrode configurations were developed. The experimental studies on the ethanol electro-spraying cone-jet characteristics in the micro-scale combustors were carried out. The size and velocity distributions of the electro-spraying droplets were measured by a Phase Doppler Anemometer for both electrode configurations. Numerical calculation was performed to investigate the effects of the ring electrode on the electric field. A non-dimensional analysis was proposed to explain the liquid electro-spraying phenomena at the cone-jet mode. The results show that the electric field strength near the nozzle tip decreased when using the ring electrode with an appropriate voltage based on the superposition principle of the electric field, and the cone-jet mode could form at lower nozzle voltage without "satellite trapping". Compared with the nozzle system without the ring electrode, the nozzle-ring system could produce smaller and more uniform droplets because of the more stable cone-jet mode. It had been observed that the lower velocity of the droplets could have smaller size in the nozzle-ring system. The dimensionless droplet size in both the nozzle system and nozzle-ring system was found to have a 1/2 power dependence on the dimensionless liquid flow rate. Highlights: A more stable cone-jet mode was obtained for the nozzle-ring system. Smaller and more uniform droplets were observed for the nozzle-ring system. The dimensionless droplet sizes have a 1/2 power dependence on dimensionless liquid flow rate. The electric field near the nozzle tip for the nozzle-ring system is smaller.